Peningkatan Kualitas Pembelajaran Melalui Penerapan Sistem Informasi Manajemen (SIM) - Ade Andriana Salsabila; Rayyan Firdaus (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The application of Management Information Systems (MIS) in the educational context has become an increasingly important topic in efforts to improve the quality of learning. MIS helps educational institutions to manage information efficiently, increase data accessibility, and improve decision-making processes. This research aims to identify how SIM can improve the quality of learning in educational institutions. The research method used is a literature study to collect information related to the application of SIM in education. The application of Management Information Systems (MIS) in the educational context has become an increasingly important topic in efforts to improve the quality of learning. MIS helps educational institutions to manage information efficiently, increase data accessibility, and improve decision-making processes. This research aims to identify how SIM can improve the quality of learning in educational institutions. The research method used is a literature study to collect information related to the application of SIM in education. Implementing MIS can provide various benefits, including increased efficiency in educational administration, monitoring student performance, and better decision making based on accurate and up-to-date data. SIM also helps in improving communication between various stakeholders in educational institutions, such as teachers, students, parents, and school management. Thus, the implementation of SIM can significantly improve the quality of learning and help educational institutions to achieve their educational goals.